Software Engineering for Space Exploration. - Lutz, Robyn (Computer (00189162), 2011)
Software engineering offers tools and techniques that improve the odds spacecraft will survive long missions, contributing to their resilience to new environmental challenges and to their adaptability to updated mission requirements.